Colletotrichum juglandis sp. nov. (Ascomycota: Glomerellaceae) associated with walnut leaf spot in China - Wei, Xin; Yang, Shu Qi; Jiang, Zhi Gang; Cui, Meng Jiao; Deng, Jian Xin; Zhang, Yi (Phytotaxa, 2022)
Colletotrichum species are destructive pathogens, saprobes and endophytes on various plant hosts. However, the species occurring on walnut remains largely unresolved. Walnut leaf spot occurred seriously in orchards of Xingshan County, Hubei Province in China. To determine Colletotrichum spp. associated with Juglans regia, 22 isolates were obtained from the diseased leaf samples collected during 2019 and 2020. Seven isolates were further selected as representatives based on morphology and phylogeny using ITS, GAPDH, CHS-1 and ACT gene regions. The results revealed that the isolates belonged to two phylogenetic species complexes, C. gloeosporioides species complex (CGSC) comprising C. gloeosporioides and C. kahawae, and C. acutatum species complex (CASC) including C. nymphaeae, C. godetiae, C. fioriniae and a new species, namely Colletotrichum juglandis sp. nov.. Among them, C. kahawae was firstly reported from walnut.